Estudo do metabolismo renal da guanilina e das interações entre guanilina e uroguanilina com os peptideos natriureticos ANP e urodilatina - Santos Neto, Messias Simões dos (1999)
Guanylin and uroguanylin share natriuretic and kaliuretic activities. While guanylin is inactivated by chymotrypsin ''in vitro'', uroguanylin resists to chymotrypsin attack. Experiments were done in the perfused rat kidney with chymostatin (a protease inhibitor - 600 µg/ml) to search for a possible renal metabolism of guanylin. E.coli heat-stable enterotoxin (STa), guanylin and uroguanylin also bind to and activate membrane guanylate-cyclase C (GC-C) expressed in the kidney and intestine. Atrial natriuretic peptide (ANP) and its renal form (urodilatin, UROD) have well known natriuretic effects and activate guanylate-cyclase A (GC-A). It is also our purposal to search for possible synergisms between ANP, UROD, guanylin and uroguanylin. At the dose used, chymostatin lacks effect in electrolyte reabsorptions. When introduced after chymostatin, guanylin lowered %TNa+ (from 81.3±1.9 to 72.7±2.45, p<.05). Guanylin (0.3 µg/ml) itself had no effects in %TNa+. We concluded that guanylin undergoes renal metabolism. Pretreatment with ANP (0.1 ng/ml) enhanced guanylin (0.3ug/ml) natriuretic activity (reduction in %TNa+; from %TNa+: 86.4±3.35% to 68.5±1.67%, p<0.05) and its kaliuretic activity (reduction in %TK+; from 76.0±6.26% to 50.4±3.13%; p<0.05), but clearly inhibited (p<0.05) uroguanylin-induced (0.5ug/ml) reduction in %TNa+ (from 64.1±2.37% to 85.2±1.93%; p<0.05), and in %TK+ (from 49.0±4.43% to 61.2±3.61%). UROD (0.1ng/ml) also enhanced the guanylin-induced natriuresis (reduction in %TNa+= 69.0±1.93%, p<0.05) and kaliuresis (%TK+= 45.8±3.61%, p<0.05), and inhibited (p<0.05) the reduction in %TNa+ of uroguanylin to 17.9±1.67 as well as its reduction %TK+ to 75.7±3.13%. The synergism between ANP and UROD with guanylin and the unexpected antagonism between ANP and UROD with uroguanylin point out to possible interactions between natriuretic peptides receptors (NPR) and GC-C-coupled receptors. The existance of other subtypes/isoforms of receptors mediating the renal actions of guanylin and uroguanylin may also be considered. These findings can have important pathophysiological consequences in states such as heart failure in which the serum levels and/or the urinary excretion of the four peptides are markedly elevated.